A filtration-assisted approach to enhance optical detection of analytes and its application in food matrices. (15th February 2021) - Lin, Zhuangsheng; Gao, Siyue; Yang, Jason Szuhao; Qu, Yanqi; Zhang, Zhiyun; He, Lili
Highlights: A filtration-assisted optical approach was developed for salt and acrylamide. The method was based on silver nanoparticle aggregation. The method can be integrated into a smartphone or camera-based device. The method has potential to be performed in low-resource and on-site settings. Abstract: Analysis of target analytes in food and environmental samples often required sophisticated instrumentation, which restrains the accessibility and portability of the analysis. Herein, we developed an instrument-free approach for rapid quantification of target analytes. The reported filtration-assisted approach enables image analysis of aggregates formed via interaction between analytes and silver nanoparticles (AgNPs). Two model analytes were chosen for aggregating AgNPs, potassium phosphate for neutralizing the charges and a di-thiol molecule (2, 2′-(ethylenedioxy) diethanethiol (EDT)) for cross-linking. The mixtures of AgNPs and analytes were filtered onto filter membranes and analyzed using grey color intensity analysis. Based on the AgNPs-EDT platform, we demonstrated the detection of 1 µg/mL acrylamide in instant coffee and biscuit matrices was achievable. The filtration-assisted method provides a simple, fast and inexpensive approach for optical detection and quantification of analytes in food matrices.